Bifacial Cu(In, Ga)Se2 solar cells using hydrogen‐doped In2O3 films as a transparent back contact. (29th May 2018) - Keller, Jan; Chen, Wei‐Chao; Riekehr, Lars; Kubart, Tomas; Törndahl, Tobias; Edoff, Marika
Abstract: Hydrogen‐doped In2 O3 (IOH) films are used as a transparent back contact in bifacial Cu(In, Ga)Se2 (CIGS) solar cells. The effect of the IOH thickness and the impact of the sodium incorporation technique on the photovoltaic parameters are studied, and clear correlations are observed. It is shown that a loss in short circuit current density ( J SC ) is the major limitation at back side illumination. The introduction of a thin Al2 O3 layer on top of the IOH significantly increases the collection efficiency (ϕ(x)) for electrons generated close to the back contact. In this way, the J SC loss can be mitigated to only ~ 25% as compared with front side illumination. The Al2 O3 film potentially reduces the interface defect density or, alternatively, creates a field effect passivation. In addition, it prevents the excessive formation of Ga2 O3 at the CIGS/IOH interface, which is found otherwise when a NaF layer is added before absorber deposition. Consequently, detrimental redistributions in Ga and In close to the back contact can be avoided. Finally, a bifacial CIGS solar cell with an efficiency (η) of η = 11.0% at front and η = 6.0% at back side illumination could be processed. The large potential for further improvements is discussed. Abstract : This contribution highlights the great potential of hydrogenated In2 O3 (IOH) films as a transparent back contact in bifacial chalcopyrite solar cells. For the best sample, an efficiency of 11% at front and 6% at back side illumination is achieved. The implementation of an Al2 O3 layer on top of IOH is proven to reduce the recombination rate at the back contact, which results in a significant improvement in photo current at back side illumination. It is further found that the Al2 O3 prevents an excessive Ga2 O3 formation and the corresponding detrimental redistribution of Ga and In in its vicinity.